SCIENTIFIC –EDUCATIONAL CLUSTER - MECHANISM OF INNOVATIVE DEVELOPMENT OF THE COUNTRY - Usmonov, Botir (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The role of the innovative community of education, science, production in growth and development is scientifically substantiated in the article. The regularity of the formation of innovation, innovation centers, innovation environment in the interrelation of the essence and content of the term cluster is highlighted. The main decision of the problems connected with increase of integration of educational efficiency and industrial sphere is possible under condition of formation educational-economical clusters, where core of this establishment are higher educational institutions, as universities create human potential of innovative development, and also involved in fundamental and applied research investigations.